1984
DOI: 10.1177/030006058401200315
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Benzydamine Hydrochloride 0·15% w/v (‘Difflam’ Oral Rinse) and Acetyl Salicylic Acid as Analgesics following Tonsillectomy

Abstract: The efficacy of 'Difflam' Oral Rinse and soluble aspirin in the post-operative management of tonsillectomy in adult patients has been compared. Whilst aspirin proved slightly more effective in relieving pain and discomfort of swallowing, 'Difflam' Oral Rinse was superior in the relief of earache, in promoting the healing of the tonsil bed and in the duration of necessity of treatment. It is therefore suggested that the two preparations might be taken concomitantly to provide quick, as well as long-lasting, pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…21 Indeed, 20% of unplanned postoperative visits following UPPP are for inadequate pain control. 22 Multimodal and alternative therapies, such as gabapentin, local anesthesia, local corticosteroid, sucralfate, selective COX-2 inhibitors, 18 and aspirin, and other nonsteroidal anti-inflammatory gargles 23 have gained traction in an effort to ease the opioid burden. Optimizing preoperative pain regimens is similarly important.…”
Section: Discussionmentioning
confidence: 99%
“…21 Indeed, 20% of unplanned postoperative visits following UPPP are for inadequate pain control. 22 Multimodal and alternative therapies, such as gabapentin, local anesthesia, local corticosteroid, sucralfate, selective COX-2 inhibitors, 18 and aspirin, and other nonsteroidal anti-inflammatory gargles 23 have gained traction in an effort to ease the opioid burden. Optimizing preoperative pain regimens is similarly important.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the occurrence of these side effects were more when the difflam spray (0.15%) was directly sprayed in the mouth for pain relief in post tonsillectomy patients. 17,18 Hung NK et al have proposed two studies for the effectiveness of BH spray applied on the endotracheal tube cuff, and sprayed over oropharynx just before intubation, in all deviating the incidence and severity of sore throat post operatively. They observed that, highest incidence of POST occurred at 6 hours after extubation.…”
Section: Discussionmentioning
confidence: 99%
“…To relieve this pain different analgesics and routes of administration, including oral, intramuscular and rectal, have been used. For example, aspirin and paracetamol orally have been compared, both providing satisfactory pain relief (Reuter and Montgomery, 1964), as did benzydamine hydrochloride orally (Irwin and Archarya, 1984) and diclofenac in suppository form (Donnerly and Basmossen, 1984). A study comparing pentazocine 50 mg and paracetamol 500 mg administered rectally (Saarnivaara, 1984), however, concluded that they provided insufficient pain relief in the immediate post-operative period.…”
Section: Discussionmentioning
confidence: 99%